Growth and body nutrient deposition of two broiler commercial genetic lines - Marcato, S. M. [UNESP] (2008)
The objective of this work was to study growth and body nutrient deposition profiles of male and female Cobb and Ross broilers using Gompertz equations. A total number of 1,920 one- to 56-day-old broilers were used. A randomized experimental design in a factorial arrangement (2 strains x 2 sex), with 4 replicates of 120 birds each, was applied. Diets were formulated to supply the nutrient requirements recommended by the genetic companies. A sample of birds was weekly weighed and sacrificed after 24 hours fasting. Carcasses were de-feathered and weighed again. The parameters of the Gompertz equation for body weight and its components (water, ashes, protein, and fat) were estimated. An interaction (p<0.05) between sex and breed was observed for mature weight (Wm) (kg), growth rate (b) (daily) and time at maximum growth rate (t*) (day) of body weight, and body water and ash. Cobb was presented earlier growth and body protein and ash deposition. Ross strain was superior in body water deposition.